Business Strategy Using The Blue Ocean Strategy Approach in Facing Competition at Lacosta Café in Metro City - Fadhilah Anas Shaabiriin; Rr Erlina; Ahmad Faisol (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research focuses on Kafe Lacosta in Kota Metro, examining its business strategy implementation using the Blue Ocean Strategy approach to navigate the increasingly competitive market landscape. The study aims to explore and evaluate how Kafe Lacosta applies the Blue Ocean Strategy framework to tackle the competition it faces. As competition in the café sector intensifies, business owners are required to adopt innovative strategies to sustain and grow their enterprises. This research adopts a descriptive qualitative method, utilizing data collection techniques such as observation, interviews, and documentation. The analysis is conducted through tools like the Four Actions Framework, the Eliminate-Reduce-Raise-Create (ERRC) grid, the Strategy Canvas, and the Blue Ocean Idea Index. The results indicate that Lacosta MSME has initiated the Blue Ocean Strategy, particularly through product innovation, service enhancement, and promotional activities. Nonetheless, pricing remains a challenge that needs further attention. In general, applying the Blue Ocean Strategy has enabled Lacosta to develop distinctive value propositions to address market competition, especially by offering affordable value to its customers.